-6(v+3)+3v+6=6v+8

Simple and best practice solution for -6(v+3)+3v+6=6v+8 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6(v+3)+3v+6=6v+8 equation:


Simplifying
-6(v + 3) + 3v + 6 = 6v + 8

Reorder the terms:
-6(3 + v) + 3v + 6 = 6v + 8
(3 * -6 + v * -6) + 3v + 6 = 6v + 8
(-18 + -6v) + 3v + 6 = 6v + 8

Reorder the terms:
-18 + 6 + -6v + 3v = 6v + 8

Combine like terms: -18 + 6 = -12
-12 + -6v + 3v = 6v + 8

Combine like terms: -6v + 3v = -3v
-12 + -3v = 6v + 8

Reorder the terms:
-12 + -3v = 8 + 6v

Solving
-12 + -3v = 8 + 6v

Solving for variable 'v'.

Move all terms containing v to the left, all other terms to the right.

Add '-6v' to each side of the equation.
-12 + -3v + -6v = 8 + 6v + -6v

Combine like terms: -3v + -6v = -9v
-12 + -9v = 8 + 6v + -6v

Combine like terms: 6v + -6v = 0
-12 + -9v = 8 + 0
-12 + -9v = 8

Add '12' to each side of the equation.
-12 + 12 + -9v = 8 + 12

Combine like terms: -12 + 12 = 0
0 + -9v = 8 + 12
-9v = 8 + 12

Combine like terms: 8 + 12 = 20
-9v = 20

Divide each side by '-9'.
v = -2.222222222

Simplifying
v = -2.222222222

See similar equations:

| 54x^2+48x+11=0 | | 315/x=4/16 | | .5x=1.56 | | 6+10x=-94 | | 2[7-6(1-n)]+9=-32+6[6(n+1)-3n] | | 2/7b=1/7 | | 0=2y-3 | | 2sin^2(x)-sin(x)-1=0 | | 4n+16=56 | | X^4+6x-108=0 | | 1/3y≥5 | | .3x-5.04=-6.3 | | f(f(x))=25x+9 | | H(t)=-16t^2+72t+5 | | 4/3(pi)10^3 | | 5y=0-10 | | x^2-10x-25=21-25 | | -38=5(2y-1) | | x+0.5=3.2 | | 0-10=5y | | -6/5x=-7 | | 1-cos(6x)=3cos(2x) | | 1/6t=4 | | Y=sin(4x) | | (-2/3)x^2-5 | | 5x^2+13-6=0 | | 10h+5=85 | | 19z-6(4z-1)= | | 20x^2+5.2x-0.5=0 | | 0=8-2y | | 6=2.5(w-2) | | 20x^2=1 |

Equations solver categories